Formulasi dan Uji Aktivitas Antioksidan Face Toner Ekstrak Etanol Daun Yakon (Smallanthus sonchifolius) Menggunakan Metode DPPH - Fika Riyanti; Bagas Ardiyantoro; Siwi Hastuti (Journal of Innovative and Creativity, 2026)
Excessive exposure to sunlight can cause the formation of free radicals that can damage skin tissue, thus requiring natural antioxidants. The use of natural ingredients as a source of antioxidants in the form of topical preparations is a potential alternative. This study aims to formulate ethanol extract of yakon leaves (Smallanthus sonchifolius) into a face toner formulation and evaluate its physical quality, antioxidant activity, and to determine the optimal concentration of the face toner formulation that can inhibit free radicals. Extraction was carried out using the maceration method with 70% ethanol, then formulated into face toner with different concentrations, namely 1%, 2%, and 3%. After that, physical quality evaluation was carried out in the form of organoleptic tests, pH tests, homogeneity tests, and viscosity tests. Antioxidant activity was tested using the DPPH method and measured using UV-Vis spectroscopy at a wavelength of 520 nm. The results showed that all formulas met the physical quality test standards and had antioxidant activity at concentrations of 1%, 2%, and 3% with IC50 values of 95.91, 93.58, and 91.70, respectively, all of which were classified as strong. while the negative control formula without extract had a value of 167 (weak category), and the positive control quercetin had a value of 9.95 (very strong category).